DISIPLIN POSITIF SEBAGAI UPAYA MENANGGULANGI PERILAKU BERMASALAH SISWA SEKOLAH DASAR - Oktafiani, Dewi Ayu; Kamal, Rahmat; Ferimeldi, Ferimeldi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
The developmental phase of students in Primary School is a period where the desire for freedom emerges within their surroundings. A positive environment has a positive impact on student behavior, while a negative environment can encourage problematic behavior. Problematic behavior can lead to issues both for the students themselves and those around them. Teachers play a crucial role in addressing problematic behavior with a managerial approach, but the use of punishment tends to have negative consequences. Therefore, this study aims to describe students' problematic behavior and analyze the implementation of positive discipline at SD Negeri 02 Pecakaran. This research is a case study with a qualitative descriptive approach, involving students from grades IV, V, and VI. Data were collected through observation, interviews, and checklist sheets. The results of this study indicate that problematic student behavior is identified in four situations, influenced by internal and external factors. The family environment is dominant as a trigger for problematic behavior. Positive discipline is considered an effective alternative solution. Through this approach, the school environment can build a culture that motivates students to behave positively without relying on negatively impactful punishments.